The effect of electrode number in electricity generation by using different type of wastewater via microbial fuel cell (MFC) / M. S. Sumairi ... [et al.] - M. S., Sumairi; M.A, A.Rahman; S.A, Raman; N.S, Azwan; O.S.J, Elhama (2018)
Instead of using- energy to treat wastewater, it is feasible to generate energy from the wastewater itself as well as treating it using a Microbial Fuel Cell (MFC). MFC generates electricity from this huge amount and various type of wastewater with the help of bacteria, The objective for this experiment is to indicates the electricity generation as well as sewage treatment in the same period to observe how MFC could improve the wastewater to ensure it safe to be release to the open water. Four cells were used where two of them consisted with POME and the balance with leachate. For each of the wastewater it consisted of single and dual anodes but the same number of cathode. The cathode and anode are made of aluminum placed in two separate chambers and the cells is completed with salt bridge made of cotton rope covered with 120 mm plastic pipe and wire to connect with voltmeter for voltage monitoring. POME and leachate with COD of 49590mg/L and 25920mg/L respectively were introduced into the cells. Voltage measurement was made twice a day for 25 days and the average value is taken into the result. COD, CFU and pH value is taken from initial of experiment and at the end of the experiment. The last voltage generate for POME was 625mv and for leachate was 388mv with both have affected by formation of colony around the anode 903x 10 11 CFU/mL in POME and 229xl 0 11 CFU/mL in the leachate. The formation of colony causes the COD in both wastewater decrease for about 52% to 61.2% percentage drop in leachate and POME. This asserted that MFC generated electricity as well as being better waste treatment devices than natural and constructed waste treatment ponds.